1997
DOI: 10.1021/bi961801a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Buried Charged Groups on Cysteine Thiol Ionization and Reactivity in Escherichia coli Thioredoxin:  Structural and Functional Characterization of Mutants of Asp 26 and Lys 57

Abstract: To investigate the role of Asp 26 and Lys 57, two conserved, buried residues, in the redox mechanism of Escherichia coli thioredoxin (Trx), three mutant proteins, Asp 26 --> Ala (D26A), Lys 57 --> Met (K57M), and the double mutant D26A/K57M, were prepared, replacing the charged amino acids with hydrophobic residues with similar sizes. Both the oxidized (Trx-S2) and reduced [Trx-(SH)2] forms of the mutant thioredoxins are fully folded and similar in overall structure to the wild-type protein (wt). The structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
237
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(251 citation statements)
references
References 53 publications
12
237
2
Order By: Relevance
“…This is in agreement with the wild-type and D26A cysteine pKa assignments of Wilson et al (1995). It is also consistent with D26A data of Dyson et al (1997), although these authors propose that either both thiols titrate with pKa between 7 and 8, or one thiol titrates with pKa near 7.8 and the other with higher than their experimental pH (>IO).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is in agreement with the wild-type and D26A cysteine pKa assignments of Wilson et al (1995). It is also consistent with D26A data of Dyson et al (1997), although these authors propose that either both thiols titrate with pKa between 7 and 8, or one thiol titrates with pKa near 7.8 and the other with higher than their experimental pH (>IO).…”
Section: Discussionsupporting
confidence: 89%
“…the active site. A similar conclusion has been reached from fluorescence studies of D26A (Hanson, 1995;Dyson et al, 1997). Figure 4 compares the Raman SH band profiles (2,500-2,650 cm" interval) of wild-type thioredoxin and D26A, each normalized appropriately to the same intensity standard (Tuma et al, 1993).…”
Section: Comparison Of D26a and Wild-type Thioredoxinsupporting
confidence: 68%
“…Cys-240 is flanked on either side by Ala-239 and Arg-241, whereas Cys-237 is sandwiched°between°Ser-236°and°Gln-238°(Figure°1).°Neigh-boring amino acids can determine thiol pK a and, thus, the chemical reactivity of an entire protein, as has been shown for the active enzymatic site of thioredoxin in which nearby Asp carboxyl and Lys amino groups influence local thiol pK a and thereby influence the rate of°thiol°disulfide°reactions°at°physiological°pH° [27]. Based on tandem-MS fragmentation experiments with mono-conjugated ZnF peptide, we observed that Cys-240 is much more reactive than Cys-237.…”
Section: Discussionmentioning
confidence: 93%
“…Cys-32 occurs near the start of an α-helix [35], is surfaceexposed and has a pK a of 7.1 [36], much lower than that of the free cysteine (pK a of 8.7 at neutral pH), rendering it highly reactive. At neutral pH the reactive sulphur atom of Cys-32 may share a hydrogen bond to the -SH hydrogen of Cys-35 [37].…”
Section: Thioredoxin and The Thioredoxin Foldmentioning
confidence: 99%
“…At neutral pH the reactive sulphur atom of Cys-32 may share a hydrogen bond to the -SH hydrogen of Cys-35 [37]. The pK a of Cys-32 is thought to be decreased by a nearby buried partial charge on Asp-26 [36,38], which may serve as a general acid\base in thioredoxin-catalysed redox reactions [39]. The Cys-32 thiolate can make a nucleophilic attack on disulphides, generating a mixed disulphide that is then disrupted by Cys-35 to produce a reduced substrate protein.…”
Section: Thioredoxin and The Thioredoxin Foldmentioning
confidence: 99%